Comparing questionnaires across cultures: Using Mokken scaling to compare the Italian and English versions of the MOLES index - Giuseppe Aleo; Annamaria Bagnasco; Roger Watson; Judith Dyson; Fiona Cowdell; Gianluca Catania; Milko Patrick Zanini; Emanuele Cozzani; Aurora Parodi; Loredana Sasso (Wiley, 2019)
Abstract Aim The aims of this study were (a) to translate the MOLES index from English to Italian and (ii) to compare the two versions using non‐parametric item response theory. Design An online survey was used to gather data. Methods Forward and back translation was used to prepare the Italian version of the MOLES which was then analysed using the non‐parametric item response theory of Mokken scaling. Results Mokken scales were found in both the English and the Italian versions of the MOLES index. However, the two scales-while the total scale score was not significantly different-showed different properties, and Mokken scaling selected different items from each scale.